Comparison of two different bowel anastomosis types using finite volume method. Issue 8 (10th June 2020) - Pirhan, Yavuz; Gök, Kadir; Gök, Arif
Abstract: The purpose of this study was to compare side-to-side and functional end-to-end anastomosis techniques that are commonly used in bowel surgery. Considering the dimensions of these two different anastomosis models, SolidWorks program was used for 3 D studies. Intra-intestinal flow analyzes were performed based on the finite volume method using Ansys Fluent, a computational fluid Dynamics (CFD) program. The flow velocity, pressure, turbulent knetic energy, turbulence vortex distribution, vortex viscosity and wall shear stresses for each model were calculated in results of the analysis for the side-to-side and functional end-to-end anastomosis technique. Due to the geometrical structure of the functional end - to - end anastomosis model, turbulence and hence the vortex formation is less than the side - to - side anastomosis technique. Because intersect area of bowels has wider in functional end - to - end anastomosis model, flow become easier than other. In surgical practice, functional end-to-end anastomosis is preferred over side-to-side anastomosis because of the low probability of leakage. It can be noted that the functional end - to - end anastomosis technique will be safer because of less turbulence, based on the data of fluid flow velocities, pressure, turbulent knetic energy, turbulence vortex distribution, vortex viscosity and wall shear stresses in the anastomosis.